Analisa Pengaruh Persepsi Kualitas dan Harga Terhadap Minat Beli (Case Study Integrated home protection) - Criest Roony; Dimas Dwi Priambodo; Habsari Candraditya A; Kukie Reinastya A; Medikatama Hestiyani (Indonesian Business Review, 2019)
In order to compete in the midst of a growing business in Indonesia, a product or service provider needs to understand many factors of consumer behavior. Among others there are factors that influence the purchase intention from the consumer side so that business can grow positively and sustain. This journal aims to explain variable of perceived quality and variable of price that affect the purchase intention variables in new products and services offered by Integrated home protection. The results of this study shows perceived quality and prices significantly affect purchase intention.